(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Among all countries that make up the Middle East, Lebanon has often suffered the consequences of all conflicts taking place in the area. In addition to that, the creation of Israel meant an added risk factor for Lebanese stability because other actors, countries and groups , used their territory to attack this inconvenient neighbor. Israel has repeatedly invaded southern Lebanon in an attempt to ensure the necessary depth and avoid continuous attacks. Whenever this happened, it subsequently meant a call to the international community due to the risk it poses to world peace. Due to that fact, United Nations sent in 1978 a contingent (UNIFIL ) in southern Lebanon , which was subsequently reinforced in 2006, since, according to their criteria, the control of this area increased the security of the country and helped stabilize the region. Despite some setbacks, time has proven the effectiveness of this right decision and the importance that Lebanon has definitely acquired in terms of peace due to the presence of the blue berets